1964
DOI: 10.1677/joe.0.0300057
|View full text |Cite
|
Sign up to set email alerts
|

Weight and Histology of the Pituitary Gland in Castrated Male Rats With Hypothalamic Lesions

Abstract: The effect of bilateral electrolytic lesions in the ventral hypothalamus at the coronal level of the posterior ventromedial nucleus and anterior premammillary nucleus on the weight and cytology of the pituitary gland of castrated male Lewis rats was investigated. All castrated rats were carrying successful intrasplenic isologous grafts of neonatal testes. The hypothalamic lesions resulted in a significant inhibition of pituitary hypertrophy in the castrated animals, but did not alter appreciably the cytology o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

1965
1965
1976
1976

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 10 publications
1
10
0
Order By: Relevance
“…Previous work (3) in similarly operated rats had suggested interference with growth hormone secretion. M ontem urro (13) has reported that lesions similar to those of the present study resulted in a 50% reduc tion of acidophils in castrated rats. The present findings on reduction of the number of acidophils suggest profound interference with growth hormone synthesis and/or storage and/or secretion, more so in the weanling rats than in those lesioned during early and late ado lescence.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Previous work (3) in similarly operated rats had suggested interference with growth hormone secretion. M ontem urro (13) has reported that lesions similar to those of the present study resulted in a 50% reduc tion of acidophils in castrated rats. The present findings on reduction of the number of acidophils suggest profound interference with growth hormone synthesis and/or storage and/or secretion, more so in the weanling rats than in those lesioned during early and late ado lescence.…”
Section: Discussionsupporting
confidence: 79%
“…Thyroids and pituitarics were fixed in 10% for malin; the thyroids were cut at 5 /t and stained with hematoxylin and eosin. Pituitaries were sectioned at 3 fi, stained with Masson's stain and at the largest cross section o f the gland, acidophils were counted in a manner similar to that described by M o n tem u r ro (13) by counting the acidophils in and bordering on the diagonal squares in nine counting zones at a magnification o f 450. The net reticule used had squares o f 1 mm side length.…”
Section: Methodsmentioning
confidence: 99%
“…The size and localization of the lesions were determined according to the atlas of De G root [1959] and inserted in individual lesion charts modified after Montemurro [1964[. In order to obtain adequate numbers of animals in each group for statistical analysis, two separate experiments were performed one month apari.…”
Section: Methodsmentioning
confidence: 99%
“…Food intake and and dorsomedial (Experiment 1, Group 2) hypothalamic lesions. Lesion charts modified after Montemurro (1964). Localization and extent of the lesions are indicated by stippling.…”
Section: Methodsmentioning
confidence: 99%